Discrete Movement Control of a Bio-Inspired Multi-Legged Robot - Nogueira, Helton S.; Oliveira, Felipe G.; Pio, José L. S. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2021: Anais do XIII Simpósio Brasileiro de Robótica e XVIII Simpósio Latino Americano de Robótica, 2021)
Bio-inspired robots have been widely used in different scenarios and applications such as disaster environments, mining industry, environmental monitoring, among others. In this sense, the locomotion control is a paramount operation for efficient and safe navigation of bio-inspired robots. Several locomotion controllers have been proposed to address the referred problem. Most of the techniques in literature represent the locomotion control through continuous systems. However, for a well-known set of events, like the movement control adjustment in different conditions, a discrete event-based approach can result in accurate and robust locomotion control. In this paper, we propose a discrete-event representation for multi-legged robot movements through finite state machines, regarding three different locomotion gaits and rotating operations. We demonstrate with indoor real-world experiments that, the proposed discrete-event representation can successfully supports multi-legged locomotion in different gait movements.